2020
DOI: 10.30525/2256-0742/2020-6-3-183-189
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Cooperation as an Innovation for Rural Development

Abstract: The purpose of this article is to investigate agricultural territories and their impact on agricultural cooperatives. In this case, the cooperative acts as a mechanism for rural development. The defining feature is that the mechanism of integrated development of rural territory to provide a comprehensive solution to the problems of the economy of the area and settlement, the formation and increase of investment attractiveness of the territory of the rural settlement and the creation of a “working” climate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
1
12
0
2
Order By: Relevance
“…The development and formation of agricultural cooperatives is a crucial stage of agricultural transformation [18]. Rural communities require effective leadership to promote the cultivation of emerging entrepreneurship ecosystems [6,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and formation of agricultural cooperatives is a crucial stage of agricultural transformation [18]. Rural communities require effective leadership to promote the cultivation of emerging entrepreneurship ecosystems [6,19].…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities require effective leadership to promote the cultivation of emerging entrepreneurship ecosystems [6,19]. Research by Shpykuliak and Sakovskas [18] demonstrated that the development and effective management of agricultural cooperatives could help solve socioeconomic issues, improve the welfare of farmers, and ensure the overall development of rural areas. Furthermore, the inheritance of local cooking techniques can be protected through the development of agricultural cooperatives [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Заявлена проблема становить науковий інтерес для багатьох дослідників, адже набуває всеохоплюючого поширення у процесі пізнання інституційних засад формування енергетичної безпеки сучасних господарських систем. Зокрема тут слід виділити наукові праці авторів щодо: кооперації -М. Туган-Барановський [13], В. Борщевський [19], М. Малік [18], Ф. Горбонос [20], О. Саковська [16]; альтернативної енергетики та формування інституційних складових її розвитку -Г. Калетнік [21], О. Шпичак [22], В. Месель-Веселяк [23], В. Іванченко [17] В інституційному механізмі розвитку альтернативної енергетики, в тому числі в аграрному секторі, виокремлюються своєю значимістю «зелені» енергетичні кооперативи. Нині український селянин відчуває істотну нестачу енергоресурсів, що залишаються досить дорогими.…”
unclassified
“…Реалізуючи цільові програми, держава повинна комплексно підтримувати потенційних учасників кооперативних відносин у сферах розвитку постачання, закупівель і збуту, переробки й транспортної інфраструктури, створювати сприятливі умови для залучення іноземних інвестицій, забезпечувати доступ до страхових та кредитних ресурсів на пільгових умовах, заохочувати молодь жити і працювати у сільській місцевості [16].…”
unclassified